2012
DOI: 10.1158/0008-5472.can-11-3246
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Vaccination Strategy That Circumvents Lymphodepletion for Effective Antitumor Adoptive T-cell Therapy

Abstract: Adoptive cell therapy (ACT) using tumor-reactive T lymphocytes is a promising approach for treating advanced cancer. Successful tumor eradication depends primarily on the expansion and survival of the adoptively transferred T cells. Lymphodepletion using total body irradiation (TBI) and administering high dose IL2 have been used with ACT to promote T cell expansion and survival to achieve maximal therapeutic effects. However, TBI and high dose IL2 increase the risk for major complications that impact overall s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…We and other investigators showed that the need for lymphodepletion, which causes major complications, can be avoided by using peptide vaccines that strongly activate adoptively transferred T cells in vivo (25,42). The novelty of the current study lies in the fact that the endogenous T cell repertoire is exploited in combination with passive injections of the anti-TRP-1 mAb TA99.…”
Section: Discussionmentioning
confidence: 99%
“…We and other investigators showed that the need for lymphodepletion, which causes major complications, can be avoided by using peptide vaccines that strongly activate adoptively transferred T cells in vivo (25,42). The novelty of the current study lies in the fact that the endogenous T cell repertoire is exploited in combination with passive injections of the anti-TRP-1 mAb TA99.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our study confirmed previous findings that lymphopenia is not a prerequisite for effective ACT (46). Several other approaches to improve ACT outcomes in the absence of irradiation and chemotherapy have been recently explored, including the use of antibodies for specific cell type depletion (46), genetically engineered tumor-specific T cells (47), Toll-like receptor (TLR) ligands (48) and other γ-chain cytokines (46,49). One foreseeable advantage of the regimen proposed in this study is the absence of CD4 + T cell ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Given these properties, IL-2/S4B6 complexes could be used therapeutically in metastatic malignancies and chronic viral infection. In support of this notion, several groups have reported favorable results using IL-2/S4B6 complexes either as a monotherapy or in combination with another agent (such as Toll-like receptor ligand, agonist anti-OX40 mAb, or peptide vaccine) in various cancer models, including B16 melanoma, Lewis lung carcinoma, MC38 colon carcinoma, MCA-205 sarcoma, and TRAMP-C1 prostate carcinoma [31,[48][49][50][51][52][53]. Moreover, IL-2/S4B6 complexes have shown efficacy in models of acute and chronic infection [54,55].…”
Section: Il-2/mab Complexesmentioning
confidence: 93%